Titanium material, heat-treatment simulation method, heat-treatment simulation apparatus, program, and method of producing titanium material
Patent Information
- Application Number
- JP2023131263
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025964000008 
Figure 2025025964000009 
Figure 2025025964000010
Abstract
Description
[Technical field]
[0001] The present application discloses a titanium material, a heat treatment simulation method, a heat treatment simulation device, a program, and a method for manufacturing a titanium material. [Background technology]
[0002] Taking advantage of their high specific strength and excellent corrosion resistance, titanium and titanium alloys are used in industrial applications such as aircraft window frames, piping and other components, electrolytic cells and heat exchangers, building materials such as roofs and roof tiles, climbing equipment such as crampons, consumer products such as golf clubs, etc. In addition, because of their good compatibility with living bodies, they are widely used in decorative items such as watches and eyeglass frames, medical applications such as implants, etc.
[0003] An example of a manufacturing process for hot-working materials made of pure titanium material or α-type titanium alloy, whose α phase is a room temperature phase, will be described. First, sponge titanium, mother alloy, titanium scrap, etc. are melted as raw materials, and an ingot is manufactured by vacuum arc melting, electron beam melting, plasma melting, etc. Next, in order to destroy the coarse structure derived from casting, the ingot is heated to the β region or α region, and is broken down by forging or rolling to produce hot-working materials such as slabs and billets. The hot-working materials are subsequently hot-rolled and processed into plates or rods. These plates and rods can be annealed and pickled to become products as they are, or further cold-rolled and annealed to remove strain according to the required dimensions and properties to become the final products. After blooming and hot working, the oxide layer and surface defects are removed by pickling or cutting.
[0004] The above-mentioned ingot is composed of coarse crystal grains with a diameter of several tens of mm. If this ingot is directly hot-rolled without performing a blooming process, the coarse crystal grains of the α phase having an hcp structure cause deformation anisotropy within the grains and between each crystal grain, resulting in unevenness on the surface at the beginning of hot rolling, which ultimately leads to deep surface defects. For this reason, after hot working, it is necessary to remove the surface defects by a descaling process or the like, which reduces the yield. This phenomenon is due to the α phase having an hcp structure with large deformation anisotropy, so in β-type titanium alloys consisting of β phases with a bcc structure and α+β-type titanium alloys with a mixed structure of β phases and α phases, the deformation anisotropy is relatively small, and the problem of surface defects is difficult to manifest.
[0005] As described above, when the blooming process is omitted for pure titanium materials or α-type titanium alloy materials in which the α phase is a room temperature phase, it is necessary to devise a way to suppress surface defects after hot rolling as much as possible. In response to this problem, methods have been proposed in which the hot working material made of an ingot is processed or heat treated, or the hot rolling method is devised to reduce surface defects.
[0006] For example, Patent Document 1 discloses a method for producing a titanium material mainly consisting of the α phase, in which the surface of an ingot is heated to a temperature of β transformation point +30°C or more and β transformation point +130°C or less from the surface to a depth of more than 5 mm, and then the ingot surface is subjected to a heat treatment in which it is cooled at a cooling rate equal to or faster than fan air cooling, and the surface is further treated to have an arithmetic mean roughness Ra of 1 to 20 μm before being hot rolled, thereby maintaining good surface properties after hot rolling.
[0007] Patent Document 2 discloses a manufacturing method for improving surface defects during β-region processing, in which a heat treatment is carried out in advance, in which the ingot is heated to a temperature of β transformation point +50°C or higher for up to 2 hours, and then cooled to a temperature of β transformation point -50°C or lower, thereby refining the crystal grains in the surface layer and suppressing surface defects due to deformation anisotropy of coarse crystal grains.
[0008] Patent Document 3 proposes a method of applying strain to refine the crystal grains near the surface of a titanium ingot, heating it to the recrystallization temperature or higher to recrystallize it to a depth of 2 mm from the surface, and then hot working it. Methods for applying strain include shot blasting, forging, and roll reduction.
[0009] Patent Document 4 proposes a hot working method in which a titanium ingot is soaked at 930 to 1000°C for 30 minutes to 2 hours, then rolled in the β single-phase temperature range at least 10% per pass, for two or more passes with a total reduction of 40% or more, and further rolled in the α single-phase region or α + β two-phase region at a temperature below the β transformation point with a reduction of 20% or more.
[0010] Although it is possible to reduce surface defects by processing or heat treating the hot-working material made of the ingot by the above-mentioned means, or by devising a hot rolling method, strict management of manufacturing conditions is required, which increases the manufacturing load, costs, and time, and may reduce the yield. In addition, in order to realize the above-mentioned heat treatment, it is necessary to consider the conditions according to the alloy composition, shape (rectangular, cylindrical) and dimensions of the ingot. In this regard, heat treatment conditions have been considered using tests using actual objects and heat transfer analysis. However, in the conventional methods, it is difficult for the heat transfer analysis results to match the thermal history actually given to the ingot, and it is difficult to obtain the desired titanium material only from the heat transfer analysis results. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent No. 6372373 [Patent Document 2] Japanese Patent Application Publication No. 8-060317 [Patent Document 3] Japanese Patent Application Publication No. 1-156456 [Patent Document 4] Japanese Patent Application Publication No. 159562 / 1983 Summary of the Invention [Problem to be solved by the invention]
[0012] In view of the above background art, the present application discloses a titanium material made of pure titanium or an α-type titanium alloy in which the main constituent phase at room temperature is the α-phase, which has large deformation anisotropy, and which has only minor surface defects even when directly hot worked without the blooming process, and a method for manufacturing the same. It also discloses a heat treatment simulation method, a heat treatment simulation device, and a program that can accurately determine appropriate heat treatment conditions for the manufacturing method. [Means for solving the problem]
[0013] The present application discloses the following aspects as means for solving the above problems. (Aspect 1) A titanium material made of pure titanium or an α-type titanium alloy, In a cross section perpendicular to the longitudinal direction, The average particle size of prior β grains in a surface layer of 10 mm is 10 mm or less, and the standard deviation of the particle size of prior β grains is 5 mm or less; The difference between the Vickers hardness at a position 10 mm from the surface and the Vickers hardness at the center of the cross section is 20 HV or more. Titanium material. (Aspect 2) In mass%, Fe: 0-0.50%, O: 0-0.40%, N: 0~0.05%, C: 0-0.08%, H: 0 to 0.013%, and Remainder: Ti and impurities having a chemical composition consisting of 2. The titanium material of embodiment 1. (Aspect 3) In mass%, Al: 4.0-6.0%, Sn: 2.0-3.0%, Fe: 0-0.05%, O: 0 to 0.20%, N: 0~0.05%, C: 0~0.10%, H: 0 to 0.020%, and Remainder: Ti and impurities having a chemical composition consisting of 2. The titanium material of embodiment 1. (Aspect 4) The cross section perpendicular to the longitudinal direction is rectangular. The titanium material according to embodiments 1 to 3. (Aspect 5) Area of the cross section perpendicular to the longitudinal direction S (mm 2 The ratio L / S of the perimeter L (mm) of the cross section to the perimeter L (mm) is 0.005 or more; The titanium material according to any one of aspects 1 to 4. (Aspect 6) The area inside the surface layer 10 mm deep contains the cast structure. The titanium material according to any one of aspects 1 to 5. (Aspect 7) A method for simulating heat treatment of pure titanium or an α-type titanium alloy, comprising: A first step predicts the transformation start time and the transformation rate of each phase for each time and temperature for the β / α transformation of the pure titanium or α-type titanium alloy when cooled or heated at a preset temperature change rate (note that in this application, the term "β / α transformation" is a concept that includes both "transformation from β phase to α phase (β ⇒ α transformation)" and "transformation from α phase to β phase (α ⇒ β transformation)", and may be either of them. The same applies below.); A second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; A heat treatment simulation method comprising: (Aspect 8) In the first step, the transformation start time is the time when the β transformation point temperature is reached, and the transformation rate of each phase is the transformation rate of β / α transformation. The heat treatment simulation method according to embodiment 7. (Aspect 9) In the first step, the transformation start time is a temperature reached time at which the equilibrium phase fraction changes in a thermodynamic calculation, and the transformation rate of each phase is a transformation rate of β / α transformation. The heat treatment simulation method of embodiment 7. (Aspect 10) In the second step, the heat transfer analysis is performed using a three-dimensional unsteady heat conduction equation. The heat treatment simulation method according to any one of aspects 7 to 9. (Aspect 11) Predicting the deformation resistance at each time based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation method according to any one of aspects 7 to 10. (Aspect 12) A prior β grain size is predicted for each time based on the temperature and phase fraction for each time obtained by the coupled analysis calculation. The heat treatment simulation method according to any one of aspects 7 to 11. (Aspect 13) A heat treatment simulation device for pure titanium or α-type titanium alloy, A first prediction unit predicts a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second prediction unit predicts the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted by the first prediction unit, and predicts the temperature change rate of the pure titanium or α-type titanium alloy and the time change rate of the phase fraction of each phase by a heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis unit that performs a coupled analysis calculation by either introducing the temperature change rate predicted by the second prediction unit into the temperature change rate in the first prediction unit, or by repeating predictions by the first prediction unit and predictions by the second prediction unit to perform convergent calculations of the transformation rate and the temperature change rate of each phase for each time and temperature; A heat treatment simulation device comprising: (Aspect 14) The transformation start time predicted in the first prediction unit is the time when the β transformation point temperature is reached, and the transformation rate of each phase is the transformation rate of β / α transformation. 14. The heat treatment simulation apparatus of embodiment 13. (Aspect 15) The transformation start time predicted in the first prediction unit is a temperature reaching time at which an equilibrium phase fraction changes in a thermodynamic calculation, and the transformation rate of each phase is a transformation rate of β / α transformation. Heat treatment simulation device according to embodiment 13 (Aspect 16) In the second prediction unit, the heat transfer analysis is performed using a three-dimensional unsteady heat conduction equation. 16. The heat treatment simulation device according to any one of aspects 13 to 15. (Aspect 17) The deformation resistance at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation device according to any one of aspects 13 to 16. (Aspect 18) The average prior β grain size of the prior β grains at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation device according to any one of aspects 13 to 17. (Aspect 19) A program for causing a computer to operate as a heat treatment simulation device, The computer includes: A first step of predicting a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; A program to execute. (Aspect 20) A method for producing a titanium material made of pure titanium or an α-type titanium alloy, comprising the steps of: Obtaining an ingot made of pure titanium or an α-type titanium alloy; Heating the ingot in a heating furnace under predetermined heating conditions; and After the heating, the ingot is cooled under predetermined cooling conditions; The heating conditions are the set temperature T 1 T β +10℃ or higher and T β +130℃ or less (where T β is the β transformation point), and the ingot is placed in the heating furnace for a time t 1 By heating for a period of time, at least the surface layer of the ingot is heated to a temperature of T β +10℃ or higher and T β The conditions are set to be below +130℃. The cooling conditions are as follows: the surface layer of the ingot is 10 mm deep, and the temperature is T β The conditions are set so that the temperature is reduced from +10℃ to 300℃ or less at a cooling rate of 5℃ / s or more. Manufacturing method of titanium material. (Aspect 21) The heating conditions are determined based on the results of a heat treatment simulation method according to any one of aspects 7 to 12. Manufacturing method of titanium material. (Aspect 22) In the heat treatment simulation method, a prior β grain size at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation, the heating conditions are predicted under which the average grain size of the prior β grains at a position 10 mm from the surface of the ingot is 10 mm or less and the standard deviation of the grain sizes of the prior β grains is 5 mm or less, and the ingot is heated according to the predicted heating conditions. Method for manufacturing the titanium material of embodiment 21 (Aspect 23) The cooling conditions are determined based on the results of the heat treatment simulation method according to any one of aspects 7 to 12. A method for producing a titanium material according to any one of aspects 20 to 22. (Aspect 24) The time t from the end of the heating to the start of the cooling 2 is determined based on the results of the heat treatment simulation method according to any one of aspects 7 to 12. A method for producing a titanium material according to any one of aspects 20 to 23. Effect of the Invention
[0014] The titanium material of the present disclosure is made of pure titanium or α-titanium alloy, the main constituent phase of which at room temperature is the α-phase, which has large deformation anisotropy, and even when directly hot-worked without the blooming process, surface defects are minor. Moreover, the manufacturing method of the present disclosure makes it possible to appropriately manufacture such titanium material. Furthermore, the heat treatment simulation method, heat treatment simulation device, and program of the present disclosure make it possible to accurately determine appropriate heat treatment conditions for the manufacturing method. [Brief description of the drawings]
[0015] [Figure 1] This shows the relationship between temperature, stress, and structure in a heat treatment simulation. [Diagram 2] The temperature dependence of the density of carbon steel (ASTM A36) and the temperature dependence of the density of pure titanium are shown. [Diagram 3] 4 shows the temperature dependence of thermal conductivity and specific heat of titanium material. [Figure 4] This is a graph comparing the actual measured values when heated to 950℃, the temperature-phase fraction coupled analysis, and the heat transfer analysis results. The lower figure shows an enlarged view of the vicinity of the β transformation point (880℃). [Diagram 5] This is a graph comparing the actual measured values when heated to 1100℃, the temperature-phase ratio coupled analysis, and the heat transfer analysis results. The lower figure shows an enlarged view of the vicinity of the β transformation point (880℃). [Figure 6] 2 shows an example of a temperature history of a heat treatment in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present inventors have completed a heat treatment simulation method that can predict the temperature history during heat treatment with high accuracy by analyzing the heating and cooling processes of pure titanium or α-type titanium alloy by coupling the temperature and phase ratio while taking into account the latent heat of β / α transformation, and a method for predicting the prior β grain size, etc. based on this temperature history. Furthermore, by utilizing this, they have completed a titanium material in which the prior β grain size in the surface layer is 10 mm or less, the standard deviation of the prior β grain size is small, and there are few surface defects during hot working, and a method for manufacturing such a titanium material from an ingot. Below, a titanium material and its manufacturing method, as well as a heat treatment simulation method, a heat treatment simulation device, and a program according to one embodiment will be described.
[0017] 1.Titanium material The titanium material of the present disclosure is made of pure titanium or an α-type titanium alloy. In addition, in a cross section perpendicular to the longitudinal direction of the titanium material, the average particle size of prior β grains in a region 10 mm deep on the surface of the cross section is 10 mm or less, the standard deviation of the particle sizes of the prior β grains is 5 mm or less, and the difference in Vickers hardness between the position 10 mm deep on the surface of the cross section and the center of the cross section is 20 HV or more.
[0018] 1.1 Chemical composition The titanium material of the present disclosure is made of pure titanium or an α-type titanium alloy. These have the α-phase, which has large deformation anisotropy, as the main constituent phase at room temperature. The chemical composition of the titanium material of the present disclosure is described as pure titanium or an α-type titanium alloy in JIS H4600 (plate and strip), JIS H4650 (rod), JIS H4670 (wire), ASTM B265 (strip, sheet, and plate), and ASTM B348 (bars and billets). For example, the titanium material of the present disclosure may have a chemical composition of, by mass%, Fe: 0-0.50%, O: 0-0.40%, N: 0-0.05%, C: 0-0.08%, H: 0-0.013%, and the balance: Ti and impurities, or may have a chemical composition of, by mass%, Al: 4.0-6.0%, Sn: 2.0-3.0%, Fe: 0-0.05%, O: 0-0.20%, N: 0-0.05%, C: 0-0.10%, H: 0-0.020%, and the balance: Ti and impurities. The balance of the chemical composition of the titanium material according to this embodiment may be Ti and impurities, as described above. Examples of impurities include, but are not limited to, Cl, Na, Mg, Ca, and B that are mixed in during the refining process, and Zr, Sn, Mo, Nb, Ta, and V that are mixed in from scrap, etc. There is no problem if the content of each impurity element is 0.1% or less and the total amount is 0.5% or less.
[0019] 1.2 Shape The shape of the titanium material of the present disclosure is not particularly limited. The titanium material may be, for example, any one of an ingot, a slab, a bloom, or a billet. The titanium material of the present disclosure may be hot worked as it is. For example, when the cross-sectional shape perpendicular to the longitudinal direction of the titanium material is rectangular, the titanium material can be hot rolled as it is to be processed into a plate, a wire, a square bar, a round bar, or the like. When the cross-sectional shape perpendicular to the longitudinal direction of the titanium material is circular, the titanium material can be hot rolled as it is to be processed into a plate, a wire, a square bar, a round bar, or the like. In this way, the titanium material of the present disclosure may be a titanium material for hot rolling. The titanium material may have a width, a thickness, and a length. In this case, the width of the titanium material may be 50 mm or more and 1500 mm or less, the thickness may be 30 mm or more and 1500 mm or less, and the length may be 0.1 m or more and 100 m or less. When the cross-sectional shape of the titanium material is circular, the width and thickness of the titanium material substantially coincide with the diameter of the circle.
[0020] The titanium material disclosed herein has a cross-sectional area S (mm 2 ) is preferably 0.005 or more. As described later, the finer the prior β grain size of the surface layer of the titanium material of the present disclosure, the less surface defects will occur during hot working. When the titanium material has a large surface area per volume during solidification in casting, the time until solidification and the cooling time after solidification are shortened, making it easier to refine the structure. For example, the greater the L / S of the titanium material, the smaller the prior β grain size of the surface layer of the titanium material. Also, in the heat treatment described later, the heat input increases, so the time required for heating is shortened, and the cooling rate increases due to the large amount of heat removed during water cooling, and the amount of transformation strain introduced increases. From the viewpoint of increasing the heat removal and heat input, the larger the L / S, the better, so there is no particular upper limit. As described above, L / S is preferably 0.005 or more, more preferably 0.006 or more, and even more preferably 0.008 or more. Furthermore, L / S may be, for example, 0.030 or less, 0.025 or less, or 0.020 or less.
[0021] 1.3 Prior β grain size and Vickers hardness According to the new findings of the inventors, the main cause of surface defects occurring in titanium material during hot working is unevenness formed in the early stage of hot working due to the deformation anisotropy of coarse grains of the α phase (hcp). In other words, in order to suppress surface defects during hot working, it is important to reduce this unevenness. According to the new findings of the inventors, in a cross section perpendicular to the longitudinal direction of a titanium material, if the average grain size of prior β grains in a region 10 mm deep on the surface is 10 mm or less, the standard deviation of the grain sizes of the prior β grains is 5 mm or less, and the difference in Vickers hardness between the position 10 mm deep on the surface and the Vickers hardness at the center of the cross section is 20 HV or more, then surface defects during hot working will be minor.
[0022] 1.3.1 Prior β grain size As-cast titanium material is usually composed of coarse crystal grains with a prior β grain size of several tens of mm. In contrast, as described above, in the titanium material disclosed herein, in a cross section perpendicular to the longitudinal direction of the titanium material, the average grain size of the prior β grains in a 10 mm region of the surface layer is 10 mm or less, and the standard deviation of the grain size of the prior β grains is 5 mm or less, that is, the surface layer has fine and uniform crystal grains. The average grain size of the prior β grains in a 10 mm region of the surface layer may be 9 mm or less or 8 mm or less. The lower limit of the average grain size of the prior β grains is not particularly limited, but may be, for example, 1 mm or more, 2 mm or more, 3 mm or more, 4 mm or more, or 5 mm or more. By having an average grain size of a certain size or more, it is expected that the deformation resistance during hot working will be reduced. Furthermore, by having the average particle size of the prior β grains be equal to or larger than a certain level and the Vickers hardness difference described later be equal to or larger than a certain level, it is expected that strain is concentrated inside at the beginning of rolling, and the internal structure is refined by the time of the subsequent rolling pass, making it difficult for defects to occur. The standard deviation of the particle size of the prior β grains may be 3 mm or less or 2 mm or less. In order to make the crystal grains of the surface layer fine and uniform in this way, for example, it is effective to give an appropriate thermal history to the surface layer of the ingot, as described later. In addition, if the simulation method of the present disclosure described later is not utilized, it is necessary to consider the conditions for giving an appropriate thermal history to the surface layer of the ingot by trial and error through actual machine testing, which requires a great deal of man-hours and labor. In addition, the present inventor has confirmed that the average particle size of the prior β grains exceeds 10 mm, the standard deviation of the particle size of the prior β grains exceeds 5 mm, and the difference in Vickers hardness between the surface layer 10 mm and the center is 20 HV or less, as shown in Comparative Examples No. 2 to No. 7 described later. This is thought to be due in part to the fact that the surface temperature reached was low and that the β to α transformation was completed during transportation until water cooling.
[0023] In the titanium material of the present disclosure, the metal structure of the region inside the 10 mm surface layer region is not particularly limited because it does not substantially affect the problem-solving mechanism of the titanium material of the present disclosure. The titanium material of the present disclosure may, for example, have a cast structure (columnar or equiaxed prior β grains of several tens of mm in size, the interior of which is composed of two or more α grains). That is, the region inside the 10 mm surface layer region may contain coarse crystal grains. The average grain size of the prior β grains in the region inside the 10 mm surface layer region may, for example, be 10 mm or more or 15 mm or more, and may be 50 mm or less or 40 mm or less. The standard deviation of the grain size of the prior β grains may be 5 mm or more or 10 mm or more, and may be 30 mm or less or 20 mm or less. Alternatively, the titanium material of the present disclosure may have a processed structure in the region inside the 10 mm surface layer region. Alternatively, in the titanium material of the present disclosure, the average particle size of the prior β grains in a region inside the surface 10 mm region may be 10 mm or less, similar to the surface 10 mm region, and the standard deviation of the particle sizes of the prior β grains may be 5 mm or less.
[0024] In this application, the "surface 10 mm region" refers to the region extending 10 mm inward from the outer edge of a cross section perpendicular to the longitudinal direction. In addition, in this application, the "average grain size" and "standard deviation" are measured as follows. That is, a cross section perpendicular to the longitudinal direction of a titanium material is observed with an optical microscope or a scanning electron microscope, and the area circle equivalent diameter is determined for each of the multiple grains (old β grains) that existed in the β region contained in the cross section, and the average value is taken as the "average grain size." In addition, the "standard deviation" is calculated by taking the square root of the mean square of the difference between each numerical value and the average value for the 100 measured grain sizes.
[0025] 1.3.2 Vickers hardness As described above, as-cast titanium material is usually composed of coarse crystal grains with a prior β grain size of several tens of mm, and the difference in strain between the surface layer and the interior is small, and the difference in Vickers hardness between the position 10 mm deep in the surface layer of a cross section perpendicular to the longitudinal direction and the center of the cross section is small. In contrast, the titanium material disclosed herein has a difference in Vickers hardness between the position 10 mm deep in the surface layer and the center of the cross section of 20 HV or more. The difference in hardness may be 25 HV or more or 30 HV or more, or may be 100 HV or less, 80 HV or less, 60 HV or less, or 40 HV or less. When the difference ΔHV between the Vickers hardness at the position 10 mm deep in the surface layer and the center is large, it can be said that strain is introduced into the surface layer. If strain is introduced into the surface layer, for example, when the steel is heated to a β single-phase region before hot working, the strain acts as a driving energy to cause a transformation from α phase to β phase (α ⇒ β transformation), which further refines the prior β grain size, suppresses the generation of cracks and voids due to strain concentration at grain boundaries during hot working, and suppresses deformation anisotropy after hot working, and makes it easier to make surface defects after rolling more harmless. In order to increase the Vickers hardness difference between the surface layer and the center in this way, it is effective to give an appropriate thermal history to the surface layer of the ingot, for example, as described below.
[0026] In this application, the "Vickers hardness at a position 10 mm from the surface" and the "Vickers hardness at the center of the cross section" are measured as follows: Vickers hardness is measured according to JIS Z 2244, with a measuring load of 1 kgf and a holding time of 15 s, and a five-point test is performed, and the Vickers hardness is calculated as the average of the three points excluding the maximum and minimum values.
[0027] 2. Titanium material manufacturing method The technology of the present disclosure also has an aspect of a method for producing a titanium material. That is, the method for producing a titanium material of the present disclosure is a method for producing a titanium material made of pure titanium or an α-type titanium alloy, comprising the steps of: Obtaining an ingot made of pure titanium or an α-type titanium alloy; Heating the ingot in a heating furnace under predetermined heating conditions; and After the heating, the ingot is cooled under predetermined cooling conditions; The heating conditions are the set temperature T1 T β +10℃ or higher and T β +130℃ or less (where T β is the β transformation point), and the ingot is placed in the heating furnace for a time t 1 By heating for a period of time, at least the surface layer of the ingot is heated to a temperature of T β +10℃ or higher and T β In other words, the heating conditions are set so that the ingot is heated to T +130°C or less in the heating furnace. β +10℃ or higher and T β +130℃ or less (where T β is the β transformation point) 1 And the time in the furnace is t 1 By heating for a period of time, at least the surface layer of the ingot is heated to a temperature of T β +10℃ or higher and T β The condition was set to be below +130°C. The cooling conditions are as follows: the surface layer of the ingot is 10 mm deep at a position of T β The conditions were set so that the temperature was cooled from +10°C to below 300°C at a cooling rate of 5°C / s or faster.
[0028] In the above manufacturing method, the heating and cooling conditions need to be optimally set depending on the chemical composition, shape (rectangular, cylindrical) and dimensions of the ingot. In this case, it is preferable to predict the optimal heating and cooling conditions by a heat treatment simulation using heat transfer analysis, and set the heating and cooling conditions in the actual operation based on the prediction results. That is, in the manufacturing method disclosed herein, it is preferable that the above heating conditions are determined based on the results of a predetermined heat treatment simulation method. The above cooling conditions may also be determined based on the results of a predetermined heat treatment simulation method, and further, the time t from the completion of the heating to the start of the cooling may be set based on the results of the predetermined heat treatment simulation method. 2 may be determined based on the results of a predetermined heat treatment simulation method. The heat treatment simulation will be described in detail later.
[0029] The manufacturing method of the present disclosure includes, for example, β +10℃) or more, (T β +130℃) or lower furnace temperature setting T 1 The specified time in the furnace is t 1 The method may include subjecting the ingot to a heat treatment for a period of time of 0.5 to 1000° C., followed by cooling at a cooling rate equal to or faster than air cooling. The surface layer of the ingot has a structure that has been heated to a temperature equal to or higher than the β transformation point in this heat treatment, transformed from α to β, and then cooled.
[0030] 2.1 Ingot The ingot made of pure titanium or α-titanium alloy may be obtained by a conventional method. The chemical composition of the ingot may be the same as that of the titanium material described above. The structure of the ingot may be as-cast. That is, the structure of the ingot may be composed of columnar or equiaxed prior β grains of several tens of mm, the interior of which is composed of two or more α grains. The ingot is preferably obtained by, for example, electron beam melting or plasma arc melting, compared to conventional consumable electrode vacuum arc remelting. This is because, whereas consumable electrode vacuum arc remelting is limited to a cylindrical shape with L / S=0.005, electron beam melting and plasma arc melting have a high degree of freedom in mold shape and can melt an ingot with the above L / S of a predetermined value or more. Furthermore, electron beam melting has a higher output than plasma arc melting and can be maintained at a high temperature after melting, which has the effect of making the temperature during solidification uniform and reducing the standard deviation of the grain size, and making it possible to remove impurities such as O, C, and N.
[0031] 2.2 Heating conditions The surface layer of the ingot is 10 mm (T β +10℃) or higher, the furnace temperature setting T 1 is (T β +10℃) or higher. In order to steadily promote the α⇒β transformation, the set temperature T 1 (T β +30℃) or higher is preferable. On the other hand, the set temperature T 1 But (T βIf the temperature exceeds +130℃, the prior β grain size exceeds 10 mm due to the β single phase temperature range and grain growth during cooling, and the prior β grain size tends to become coarser than before the heat treatment. 1 But (T β If the temperature exceeds 130℃, the steel reacts with oxygen in the air to form a thick, hard oxygen-rich layer on the surface of the ingot, which can cause cracks and indentations during hot rolling, and additional care such as cutting with a machine or grinding with a grinder is required. 1 But (T β +10℃) or more, (T β By keeping the temperature below +130℃, it is possible to suppress oxidation of the surface layer of the ingot while also making the surface grain fine.
[0032] Time in the heating furnace t 1 The temperature at which the ingot reaches the set temperature T 1 The time it takes for the titanium ingot to be heated in the heating furnace is determined by the size, shape and heating method of the ingot. Naturally, the heat applied to the surface layer will diffuse to the inside. If the ingot is large or has a cylindrical shape with a small (surface area / volume) ratio, the heat diffusion from the surface layer to the inside is small, so the ingot time t 1 becomes longer.
[0033] 2.3 Cooling conditions It is difficult to sufficiently reduce surface defects after hot working by only refining the grains of the surface layer by the above heating. β Cooling strain is introduced into the surface layer by setting the cooling rate from +10°C to 300°C or less to 5°C / s or more. By cooling in this manner, when the material is heated to the β single phase region before the subsequent hot rolling, the cooling strain serves as the driving energy for an α to β transformation, which further refines the prior β grain size, suppresses deformation anisotropy after hot working, and neutralizes surface defects after rolling. The method of rapid cooling is selected according to the dimensions and shape of the titanium material. For example, cooling with a fan, cooling with He, Ar or N 2 The cooling method may be at least one selected from gas cooling using an inert gas such as argon, mist cooling, and water cooling by immersion in water. When cooling by immersion in water, water can be circulated by using a pump or the like.
[0034] The presence or absence of cooling strain in the surface layer can be confirmed by the difference ΔHV in Vickers hardness between 10 mm from the surface and the center of the cross section. Vickers hardness is affected by the cooling rate and prior β grain size, but if the Vickers hardness at 10 mm from the surface is 20 HV or more higher than that at the center of the cross section, then it can be said that the effects of cooling strain, in addition to grain refinement, are clearly evident, and the targeted cooling strain has been introduced.
[0035] 2.4 Notes on time The above heating and cooling can reduce surface defects after hot rolling, but (T β +10℃) or more, (T β +130℃) or less in the set temperature range t 1 If the time t is not set appropriately, the prior β grain size at the surface layer 10 mm position will vary, and problems such as misrolling will occur during hot rolling. In particular, in the heat treatment of an ingot with a rectangular cross section, the long side of the cross section perpendicular to the longitudinal direction is more difficult to heat and cool than the short side. For this reason, the time t 1 When the length is short, the temperature of the surface layer of either the long side or the short side at a position 10 mm below the β transformation point before cooling, so T β The cooling rate from +10°C to 300°C or less cannot be set to 5°C / s or more, and it becomes difficult to introduce cooling strain into the surface layer. Therefore, the effect of refining the prior β grain size cannot be obtained during heating before the subsequent hot rolling, and surface defects may occur after rolling. In this way, when hot rolling an ingot having an edge with a larger prior β grain size and deformation anisotropy than other parts, if the edge is a side perpendicular to the roll contact surface, unevenness occurs due to the deformation anisotropy, resulting in surface defects. In addition, if the edge is the roll contact surface, problems such as warping due to deformation anisotropy that leads to rolling stop may occur, and material properties after hot rolling will vary. In the manufacturing method disclosed herein, such problems can be more appropriately suppressed by setting appropriate heating conditions based on the results of a heat treatment simulation described below.
[0036] In addition, the time from the end of heating to the start of cooling t 2 If the time is too long, the surface temperature will rise to T before cooling begins. β If the temperature drops below t, the β to α transformation will be completed, and the above-mentioned effect of rapid cooling will become difficult to obtain. 2 may correspond to, for example, the transport time from the heating step to the cooling step. In the manufacturing method of the present disclosure, the appropriate time t until the start of cooling is determined based on the results of a heat treatment simulation described later. 2 should be set.
[0037] 2.5 Details of heat treatment simulation As described above, one of the features of the titanium material of the present disclosure is that the prior β grains in the surface layer of the region of 10 mm are fine and uniform. In order to obtain such a titanium material, in the manufacturing method of the present disclosure, for example, the ingot is placed in the furnace for a time t 1 The inventors have selected (T β +10)℃ or higher, (T β +130℃) or less in the set temperature range t 1 As a method for appropriately predicting and selecting the grain size, a method for calculating the prior β grain size of pure titanium or α-type titanium alloy was examined. 1 In the study of, it is important to have high calculation accuracy of temperature, consideration of β / α transformation, and high prediction accuracy of prior β grain size. Conventional heat transfer analysis only analyzes heat conduction caused by temperature gradient, so for titanium, which generates a large transformation latent heat with β / α transformation, calculation accuracy is low near the transformation point, and β / α transformation during heating and cooling cannot be determined, which causes problems with low prediction accuracy of prior β grain size.
[0038] On the other hand, in the analysis of heat treatment of steel, an analysis has been devised and implemented that couples the temperature distribution, stress, deformation, and phase transformation of the part undergoing heat treatment, as shown in Figure 1. Phase transformation is considered to be an isothermal transformation that progresses over a very short time from austenite to ferrite, pearlite, bainite, and martensite, and is analyzed using an isothermal transformation diagram and the rate of isothermal transformation progression. The transformation latent heat during the phase transformation is taken into account in the heat transfer analysis, and the transformation strain is taken into account in the elastic-plastic analysis. In addition, efforts have been made to consider the stress dependency of the transformation rate. Therefore, we applied these to the heat transfer analysis of pure titanium or α-type titanium alloy, and investigated the prediction of prior β grain size using the obtained temperature history.
[0039] Figure 2 shows the temperature dependence of the density of carbon steel and the density of pure titanium. 1 At the β transformation point (approximately 727°C), the density changes significantly due to the α / γ transformation. Therefore, the strain (transformation strain) caused by the transformation is large, and the residual stress generated during quenching from the γ region may affect the durability of the product. On the other hand, in pure titanium and α-type titanium alloys, although β / α transformation occurs at the β transformation point (approximately 880°C), no significant change in density is observed. Therefore, the transformation strain is smaller than that of steel, and it is considered that the effect on the stress state is small. In other words, the effect of the volume change due to the transformation is small during heating as well as during cooling, and does not need to be considered, but it is considered that the latent heat associated with the transformation needs to be considered. By considering the transformation latent heat, the accuracy of the temperature-structure coupling simulation is improved, and it is considered that pure titanium material or α-type titanium material with a stable structure that has a strong influence on the material properties and defects during manufacturing can be provided. Furthermore, it is considered that pure titanium material or α-type titanium material with a stable structure can be provided by determining the timing of the β / α transformation and cooling it, or by performing processing at the optimal timing for the proportion of the β phase, which has better workability than the α phase (performing processing when the ratio has a deformation resistance suitable for processing).
[0040] Based on the above technical concept, the present application discloses the following heat treatment simulation method. That is, the heat treatment simulation method disclosed herein is a heat treatment simulation method for pure titanium or an α-type titanium alloy, comprising the steps of: A first step of predicting a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; The present invention includes the steps of: wherein, in the first step, the transformation start time is the time when the β transformation point temperature is reached, and the transformation rate of each phase may be the transformation rate of β / α transformation, i.e., the transformation rate from α phase to β phase (α ⇒ β transformation rate) during heating, and the transformation rate from β phase to α phase (β ⇒ α transformation rate) during cooling. In addition, in the second step, the heat transfer analysis may be performed using a three-dimensional unsteady heat conduction equation. In addition, in the heat treatment simulation method of the present disclosure, the deformation resistance at each time may be predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. In addition, the prior β grain size at each time may be predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation.
[0041] 2.5.1 First step In the first step, the transformation start time and the transformation rate of each phase for each time and temperature for the β / α transformation of the pure titanium or α-type titanium alloy when cooled or heated at a preset temperature change rate are predicted. Hereinafter, the prediction method of the transformation start time and the prediction method of the transformation rate of each phase for each time and temperature will be explained in order. Note that the transformation rate of each phase may be predicted for all the constituent phases that can be contained in the pure titanium or α-type titanium alloy, but in the following explanation, as an example, the prediction of the transformation rate of the transformation from the β phase to the α phase (β ⇒ α transformation) during cooling will be explained. Note that the initial value of the preset temperature change rate may be obtained by heat transfer analysis from the temperature distribution at the immediately preceding time. In addition, the following prediction method can also be easily applied to the transformation from the α phase to the β phase (α ⇒ β transformation) during heating.
[0042] When pure titanium is cooled from the β single phase region, plate-shaped α phase (α grains) precipitate (diffusion transformation) from the grain boundaries of the β phase toward the grain interior. Among the α grains, clusters that are aligned in the same direction are called colonies. Since the β / α diffusion transformation starts immediately after the β transformation point is reached, the timing of the transformation start may be the time when the β transformation point is reached. The β / α transformation of pure titanium type 1 is completed in a narrow temperature range of 875 to 880 ° C. With an increase in the added elements, the temperature range in which the α + β two-phase region is reached becomes wider. In this range, the timing of the transformation start of the β / α diffusion transformation may be assumed to be, for example, the temperature at which the equilibrium phase fraction obtained from thermodynamic calculation changes. In other words, in the first step, the transformation start time may be the time when the temperature at which the equilibrium phase fraction changes in the thermodynamic calculation is reached, and the transformation rate of each phase may be the transformation rate of the β / α transformation.
[0043] To predict the rate of diffusion transformation (transformation rate) from the β phase to the α phase, for example, the following equation, which is a modified version of the Johnson-Mehl equation, is used.
[0044]
number
[0045] Here, f(T) and n(T) are material constants, and are functions that depend on the alloy type and temperature T. For JIS Class 1 and JIS Class 2 pure titanium, f(T) = 2.0 and n = 2.0 are appropriate.
[0046] 2.5.2 Second step In the second step, the amount of transformation latent heat associated with the β / α transformation is predicted for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and the temperature change rate of the pure titanium or α-type titanium alloy and the time change rate of the phase fraction of each phase are predicted by a heat transfer analysis using the predicted amount of transformation latent heat. In the heat treatment simulation of the present disclosure, the above-mentioned analysis of phase transformation in the first step and the analysis of temperature according to the heat conduction equation in the second step may be coupled. In the second step, the heat transfer analysis may be performed using a three-dimensional unsteady heat conduction equation used in general finite element methods (FEM) and the like. An example of a three-dimensional unsteady heat conduction equation is shown below.
[0047]
number
[0048] where ρ is density, c p : specific heat at constant pressure, k: thermal conductivity, T: temperature, t: time, Q: amount of heat generated. Note that the heat conduction equation used in the second step is not limited to equation (1), and a non-steady heat conduction equation for a two-dimensional body, one-dimensional body, or axisymmetric body may be used depending on the shape of the simulation object. In addition, on the surface of the simulation object, heat transfer from different materials taking into account convection, radiation, and contact resistance may be considered.
[0049] The amount of heat generated Q takes into account Joule heat due to induction heating, heat generated by plastic deformation work, and the like, as well as the transformation latent heat associated with phase transformation, which is described by the following formula.
[0050]
number
[0051] Here, H βα : latent heat of transformation from β phase to α phase, ξ i β and α phase volume fractions. These volume fractions of the β and α phases can be obtained from the transformation rates for each temperature predicted in the first step.
[0052] In addition, pure titanium and α-type titanium alloys during the heat treatment process are considered to be mixtures of these two phases, and the linear mixture rule can be applied to physical quantities such as specific heat and thermal conductivity. In other words, the physical quantity C used in heat transfer analysis is given by the following formula. C in formula (3) i is i The physical quantity C given by equation (3) includes ρ and C in equation (1). p and k.
[0053]
number
[0054] By using equation (3), it is possible to predict not only physical quantities but also macroscopic mechanical properties, such as deformation resistance and fatigue properties.
[0055] 2.5.3 Coupled analysis steps The above-mentioned coupled analysis of temperature and phase transformation can be applied to both explicit and implicit methods. As an explicit method, the temperature change rate of pure titanium or α-type titanium alloy predicted in the second step is introduced into the temperature change rate in the first step to perform coupled analysis calculation. As an implicit method, the first and second steps are repeated to perform convergence calculation of the transformation rate and temperature change rate of each phase for each time and temperature to perform coupled analysis calculation. In the heat treatment simulation method disclosed herein, calculations may be performed by either method. In addition, the simulation method disclosed herein can be applied to simulations that consider not only heat treatment but also plastic deformation at the same time.
[0056] Regarding the heat treatment simulation disclosed herein, it is possible to perform the simulation not only using original programs using languages such as Fortran and C, but also using the finite element method (FEM) by defining the temperature T as the linear sum of the temperature vector φ at each junction and a weighting function N based on the Galerkin method.
[0057] By such a coupled analysis of temperature and phase fraction, it is possible to predict the history of temperature and phase fraction during heat treatment with higher accuracy than conventional heat transfer analysis. An example of a method for predicting the prior β grain size using the temperature and phase fraction predicted in this way will be further described below.
[0058] In the α single-phase region and the β single-phase region, the α grains and the β grains grow according to the following n-th power law:
[0059]
number
[0060] where d 0 : initial particle size, d: particle size after being held at temperature T for t seconds, R: gas constant, C, Q: material constants.
[0061] Also, particle size d p The grain size after transformation from the parent phase d s can be predicted by the following prediction formula, which assumes that the grain boundary surface is the nucleation site.
[0062]
number
[0063] Here, Is is the nucleation rate and G is the growth rate. In this way, the prior β grain size at each time can be predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation.
[0064] As described above, in the manufacturing method of the present disclosure, the heating conditions can be determined based on the results of the heat treatment simulation method. For example, the heat treatment simulation method can be used to accurately predict the prior β grain size of the surface layer of the ingot, and the in-furnace time t 1 It is preferable to determine the heating conditions such as the above. More specifically, in the above heat treatment simulation method, the prior β grain size at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation, the heating conditions under which the average grain size of the prior β grains at a position 10 mm from the surface of the ingot is 10 mm or less and the standard deviation of the grain size of the prior β grains is 5 mm or less are predicted, and the ingot is actually heated according to the predicted heating conditions. Furthermore, according to the above heat treatment simulation method, by taking into account the transformation latent heat, the thermal history imparted to the surface layer of the ingot during cooling can also be accurately predicted. That is, in the manufacturing method of the present disclosure, for example, the above cooling conditions may be determined based on the results of the above heat treatment simulation method. Furthermore, according to the above heat treatment simulation method, the temperature change of the surface layer of the slab from heating to cooling can also be accurately predicted, and the optimal time t from heating to the start of cooling can be determined. 2 That is, in the manufacturing method of the present disclosure, for example, the time t until the start of cooling can be determined based on the results of the heat treatment simulation method. 2 may be determined.
[0065] 3. Heat treatment simulation method The heat treatment simulation method of the present disclosure is not limited to being applied when determining the heat treatment conditions when manufacturing the titanium material as described above. The technology of the present disclosure also has an aspect as a heat treatment simulation method for pure titanium or α-type titanium alloy itself. That is, the heat treatment simulation method of the present disclosure is characterized by comprising the above-mentioned first step, second step, and coupled analysis step. Details of each step are as described above. For example, in the heat treatment simulation method of the present disclosure, in the first step, the transformation start time may be the time when the β transformation point temperature is reached, and the transformation rate of each of the phases may be the transformation rate of β / α transformation. In addition, in the first step, the transformation start time may be the time when the temperature at which the equilibrium phase fraction changes in the thermodynamic calculation is reached, and the transformation rate of each of the phases may be the transformation rate of β / α transformation. In addition, in the second step, the heat transfer analysis may be performed using a three-dimensional unsteady heat conduction equation. In addition, in the heat treatment simulation method of the present disclosure, the deformation resistance at each time may be predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. In addition, the prior β grain size at each time may be predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation.
[0066] 4.Heat treatment simulation equipment The technology of the present disclosure also has an aspect of a heat treatment simulation device for pure titanium or α-type titanium alloy. That is, the heat treatment simulation device for pure titanium or α-type titanium alloy of the present disclosure is: A first prediction unit predicts a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second prediction unit predicts the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted by the first prediction unit, and predicts the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis unit that performs a coupled analysis calculation by either introducing the temperature change rate predicted by the second prediction unit into the temperature change rate in the first prediction unit, or by repeating predictions by the first prediction unit and predictions by the second prediction unit to perform convergent calculations of the transformation rate and the temperature change rate of each phase for each time and temperature; That is, in the heat treatment simulation device of the present disclosure, the first prediction unit performs the first step described above. Also, the second prediction unit performs the second step described above. Furthermore, the coupled analysis unit performs the coupled analysis step described above.
[0067] As described above, the heat treatment simulation device of the present disclosure may be such that the transformation start time predicted in the first prediction unit is the time when the β transformation point temperature is reached, and the transformation rate of each of the phases is the transformation rate of β / α transformation. The transformation start time predicted in the first prediction unit may be the time when the temperature at which the equilibrium phase fraction changes in the thermodynamic calculation is reached, and the transformation rate of each of the phases is the transformation rate of β / α transformation. The heat transfer analysis may be performed in the second prediction unit by utilizing a three-dimensional unsteady heat conduction equation. The heat treatment simulation device may be configured to predict the deformation resistance at each time based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. Furthermore, the heat treatment simulation device may be configured to predict the prior β grain size at each time based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The simulation device of the present disclosure is provided with at least a central processing unit as hardware, and it is preferable that the above-mentioned first prediction unit, second prediction unit, coupled analysis unit, etc. are realized as functions of the central processing unit.
[0068] 5. Program The technology of the present disclosure also has an aspect of a program for causing a computer to operate as a heat treatment simulation device. A first step of predicting a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; a second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; The details of each step are as described above.
[0069] 6. Manufacturing method of hot-worked materials The titanium material of the present disclosure can be used, for example, as a material for hot-worked materials (for example, hot-rolled materials). In particular, by using the titanium material of the present disclosure, a hot-worked material with few surface defects can be manufactured without applying mechanical energy. That is, the manufacturing method of the hot-worked material of the present disclosure includes obtaining a titanium material by the method of the present disclosure and hot-working the titanium material without applying mechanical energy. The "application of mechanical energy" here refers to forging, which applies pressure to a metal using a die to cause plastic deformation, shot blasting, which hits particles of metal or sand with the purpose of smoothing the surface layer or applying strain to the surface layer, roll pressing, etc. The "hot processing" is, for example, hot rolling.
[0070] As described above, the titanium material of the present disclosure has a large difference ΔHV in Vickers hardness between the surface layer at 10 mm and the center, and it can be said that strain is introduced into the surface layer without applying mechanical energy such as forging. When strain is introduced into the surface layer, for example, when heated to a β single-phase region before hot working, the strain acts as driving energy to cause a transformation from α phase to β phase (α ⇒ β transformation), and the β grain size becomes finer, suppressing the occurrence of cracks and voids due to concentration of strain at grain boundaries during hot working and deformation anisotropy after hot working, making it easier to make surface defects after rolling more harmless. The hot working conditions may be the same as conventional conditions. EXAMPLES
[0071] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples. The present invention can adopt various conditions as long as it does not deviate from the gist of the invention and achieves its object.
[0072] 1. Study on improving the accuracy of heat treatment simulation 1.1 Experimental Method To verify the accuracy of the heat treatment simulation, a K-type thermocouple was placed in the center of the 75 x 30 x 125 mm surface to measure the temperature of a pure titanium slab. The slab was then inserted into an atmospheric furnace at 950°C and 1100°C and allowed to cool in the air.
[0073] 1.2 Analysis method To analyze the temperature of the pure titanium slab, a heat transfer analysis (conventional analysis) and an analysis that couples the temperature and phase ratio (analysis of this disclosure) were performed. In the analysis, the density was a constant value (4.506 g / cm 3 ), and the thermal conductivity and specific heat were taken into consideration with the temperature dependence shown in Figure 3. For comparison, a heat transfer analysis was performed using the measured specific heat, a specific heat adjusted to the measured value, and a temperature-phase ratio coupled analysis was performed using the specific heat from which the transformation latent heat was removed and the transformation latent heat (111.8 kJ / kg).
[0074] 1.3 Analysis results The β transformation point of pure titanium is approximately 880°C. When heated to 950°C, the rate of temperature change decreased in the range of 880-900°C, and in the range of 900-920°C, when heated to 1100°C. As shown in Figures 4 and 5, in the heat transfer analysis using the specific heat adjusted for the analysis, the temperature was constantly changing, and the temperature change measured near the β transformation point could not be reproduced. In contrast, as a result of performing a coupled analysis of temperature and specific heat, the temperature history measured in the actual measurement, including the decrease in the rate of temperature change at the β transformation point, was reproduced with good accuracy.
[0075] 2.Verification of the effect of improving the accuracy of heat treatment simulation 2.1 Heat treatment conditions and hot rolling conditions Rectangular ingots of pure titanium or α-type titanium alloy obtained by electron beam melting were heat-treated and water-cooled in air using a heating furnace under various conditions. The time t1 in the heating furnace was selected by predicting the prior β grain size in the cross section using the heat treatment simulation method that takes into account the transformation latent heat described above, and the conditions under which the desired pure titanium material or α-type titanium alloy material could be obtained were selected. The crystal structure and Vickers hardness difference of the obtained titanium material were investigated, and then the material was heated to 950°C and hot-rolled into a φ140mm round bar, and the surface defects were investigated. The results are shown in Table 1. The hot rolling was performed using a box rolling machine, and the ingot was rotated appropriately to introduce appropriate strain to the long and short sides.
[0076] 2.2 Observation of crystal structure The crystal structure was measured by measuring the number of grain boundaries per 120 mm length parallel to the surface twice at a depth of 10 mm from the surface along the four sides of the cross section perpendicular to the longitudinal direction of the titanium material obtained, and the average prior β grain size and standard deviation were calculated. However, when the prior β grain size exceeded 10 mm, the number of grain boundaries per 300 mm length was measured.
[0077] 2.3 Vickers hardness measurement The Vickers hardness was measured five times with a load of 1 kg at a position 10 mm deep from the surface and at the center of a cross section perpendicular to the longitudinal direction of the obtained titanium material, and the average of the three points excluding the maximum and minimum was calculated.
[0078] 2.4 Evaluation of surface defects after hot rolling The occurrence of surface defects after hot rolling was measured by cutting the hot-rolled round bar perpendicular to the longitudinal direction, polishing the cut surface to a micro-mirror finish (▽▽▽), and measuring the depth of the defects. Converted per 1m of circumference after hot rolling, cases where there was one or more surface defects 3mm or more in length, or more than 15 surface defects less than 3mm in depth, were rated as ×, cases where there were 8 to 15 surface defects less than 3mm in depth were rated as "△", and cases where there were 8 or less defects less than 3mm in depth were rated as "〇". Among the surface defects rated as "×", coarse cracks 5mm or more in depth were also observed. Even in the case of "△", there was still sufficient improvement effect, and the defects could be neutralized by slightly increasing the amount of surface cutting, and the decrease in yield was also small.
[0079] 2.5 Results and Discussion In conventional process No. 1, which implemented the blooming process, the surface defects after hot rolling were minor. This is because blooming process breaks up the coarse structure caused by casting, refines the prior β grain size both inside and on the surface, and suppresses the deformation anisotropy on the surface during hot working.
[0080] In Comparative Example No. 2, which did not undergo the blooming process, the temperature of the entire surface layer was low due to the short time spent in the furnace. In Comparative Example No. 3, the temperature of the short side (200 mm side of the 300 x 200 mm cross section) was low due to the short time spent in the furnace, Comparative Example No. 4, the temperature of the long side (400 mm side of the 400 x 300 mm cross section) was low, Comparative Example No. 6, the temperature of the long side (650 mm side of the 650 x 600 mm cross section) was low, and Comparative Example No. 7, the temperature of both sides was low. In the sides with low temperatures, the β ⇒ α transformation was completed during transportation to water cooling, so the frequency of nucleation during transformation was low and the fine grain effect was not obtained. In Comparative Example No. 5, the temperature was sufficient, but the transportation time to water cooling was long, so the β ⇒ α transformation was completed during transportation, so the frequency of nucleation during transformation was low and the fine grain effect was not obtained. The above conditions may occur if heat treatment simulation is not used, and coarse grains of 10 mm or more remain in some parts of the surface layer, the average prior β grain size exceeds 10 mm, or the standard deviation of the prior β grain size exceeds 5 mm. Furthermore, after the subsequent hot rolling, many surface defects occur, mainly around the edges where the coarse grains remain.
[0081] On the other hand, in Examples 8 to 18, in which the heat treatment conditions were determined using a heat treatment simulation, it is believed that the entire 10 mm from the surface layer of the ingot was water-cooled from the β single phase region by appropriate heat treatment, resulting in a cooling rate of 5°C / s or more (see, for example, FIG. 6). Therefore, a uniform titanium material was obtained in which the average prior β grain size in the surface layer was 10 mm or less and the standard deviation of the prior β grain size was 5 mm or less. Furthermore, in Examples 8, 10, and 13 to 16, the surface defects in the subsequent hot rolling were very minor. In Example 11, the grains grew during cooling due to the long residence time in the furnace, resulting in a slightly large prior β grain size, and therefore the frequency of surface defects increased slightly, but a sufficient improvement effect was obtained compared to the comparative example. In Examples 9 and 12, a sufficient cooling rate was obtained, resulting in a refinement effect in the surface layer, but a thick oxide layer was formed in the surface layer due to the long residence time in the furnace. Therefore, when hot rolling was performed with the oxide layer remaining, the oxide layer with low ductility was pushed in and many surface defects occurred. On the other hand, surface defects were improved by performing pre-hot rolling to cut the oxide layer. However, cutting hard titanium oxide causes severe tool wear, so Examples 9 and 12 were less efficient than the other Examples. Also, Examples 17 and 18 had a lower area S (mm 2 Since the ratio L / S of the circumference L (mm) of the cross section to the circumference L (mm) was small, the time until solidification during melting was long, and the heating time required to prevent the transformation from β to α during transportation to water cooling was also long, so the prior β grain size became somewhat large. For Example No. 17, as with Example No. 11, the prior β grain size was close to 10 mm, so the frequency of surface defects increased compared to the other Examples, but a sufficient improvement effect was obtained compared to the Comparative Examples.
[0082] [Table 1]
[0083] In the above embodiment, a rectangular ingot of titanium material is processed into a round bar by hot rolling, but the technology of the present disclosure is not limited to this embodiment. It is believed that the effects of the technology of the present disclosure are exerted regardless of the shape of the titanium material or hot-worked material.
Claims
1. A titanium material made of pure titanium or an α-type titanium alloy, In a cross section perpendicular to the longitudinal direction, The average particle size of prior β grains in a surface layer of 10 mm in a region is 10 mm or less, and the standard deviation of the particle size of the prior β grains is 5 mm or less; The difference between the Vickers hardness at a position 10 mm from the surface and the Vickers hardness at the center of the cross section is 20 HV or more. Titanium material.
2. In mass percent, Fe: 0 to 0.50%, O: 0 to 0.40%, N: 0-0.05%, C: 0-0.08%, H: 0 to 0.013%, and The balance is Ti and impurities. having a chemical composition consisting of The titanium material according to claim 1.
3. In mass percent, Al: 4.0-6.0%, Sn: 2.0 to 3.0%, Fe: 0 to 0.05%, O: 0-0.20%, N: 0-0.05%, C: 0-0.10%, H: 0 to 0.020%, and The balance is Ti and impurities. having a chemical composition consisting of The titanium material according to claim 1.
4. The cross section perpendicular to the longitudinal direction is rectangular. The titanium material according to any one of claims 1 to 3.
5. Area of the cross section perpendicular to the longitudinal direction S (mm 2 The ratio L / S of the perimeter L (mm) of the cross section to the perimeter L (mm) is 0.005 or more; The titanium material according to any one of claims 1 to 3.
6. The region inside the position of 10 mm from the surface layer contains a cast structure. The titanium material according to any one of claims 1 to 3.
7. A method for simulating heat treatment of pure titanium or an α-type titanium alloy, comprising: A first step of predicting a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; A heat treatment simulation method comprising:
8. In the first step, the transformation start time is the time when the β transformation point temperature is reached, and the transformation rate of each phase is the transformation rate of β / α transformation. The heat treatment simulation method according to claim 7 .
9. In the first step, the transformation start time is a temperature arrival time at which an equilibrium phase fraction changes in a thermodynamic calculation, and the transformation rate of each phase is a transformation rate of a β / α transformation. The heat treatment simulation method according to claim 7.
10. In the second step, the heat transfer analysis is performed using a three-dimensional unsteady heat conduction equation. The heat treatment simulation method according to any one of claims 7 to 9.
11. Predicting the deformation resistance at each time based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation method according to any one of claims 7 to 9.
12. Predicting the prior β grain size at each time based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation method according to any one of claims 7 to 9.
13. A heat treatment simulation device for pure titanium or α-type titanium alloy, A first prediction unit predicts a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second prediction unit predicts the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted by the first prediction unit, and predicts the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis unit that performs a coupled analysis calculation by either introducing the temperature change rate predicted by the second prediction unit into the temperature change rate in the first prediction unit, or by repeating predictions by the first prediction unit and predictions by the second prediction unit to perform convergence calculations of the transformation rate and the temperature change rate of each phase for each time and temperature; A heat treatment simulation device comprising:
14. The transformation start time predicted in the first prediction unit is the time when a β transformation point temperature is reached, and the transformation rate of each phase is a transformation rate of a β / α transformation. The heat treatment simulation device according to claim 13.
15. The transformation start time predicted by the first prediction unit is a temperature reaching time at which an equilibrium phase fraction changes in a thermodynamic calculation, and the transformation rate of each phase is a transformation rate of a β / α transformation. The heat treatment simulation device according to claim 13.
16. In the second prediction unit, the heat transfer analysis is performed using a three-dimensional unsteady heat conduction equation. The heat treatment simulation device according to any one of claims 13 to 15.
17. The deformation resistance at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation device according to any one of claims 13 to 15.
18. The prior β grain size at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation. The heat treatment simulation device according to any one of claims 13 to 15.
19. A program for causing a computer to operate as a heat treatment simulation device, The computer includes: A first step of predicting a transformation start time and a transformation rate of each phase for a β / α transformation of the pure titanium or α-type titanium alloy at each time and temperature when the pure titanium or α-type titanium alloy is cooled or heated at a preset temperature change rate; A second step of predicting the amount of transformation latent heat associated with the β / α transformation for each time and temperature based on the transformation rate of each phase for each time and temperature predicted in the first step, and predicting the temperature change rate and the time change rate of the phase fraction of the pure titanium or α-type titanium alloy by heat transfer analysis using the predicted amount of transformation latent heat; a coupled analysis step of performing a coupled analysis calculation by either introducing the temperature change rate predicted in the second step into the temperature change rate in the first step, or by repeating the first step and the second step to perform a convergence calculation of the transformation rate and the temperature change rate of each phase for each time and temperature; A program to execute.
20. A method for producing a titanium material made of pure titanium or an α-type titanium alloy, comprising the steps of: Obtaining an ingot made of pure titanium or an α-type titanium alloy; Heating the ingot in a heating furnace under predetermined heating conditions; and After the heating, the ingot is cooled under predetermined cooling conditions; The heating conditions are a set temperature T 1 T β +10℃ or higher and T β +130°C or less (where T β is the β transformation point), and the ingot is placed in the heating furnace for a time t 1 By heating for a period of time, at least a surface layer of 10 mm of the ingot is heated to a temperature of T β +10℃ or higher and T β The conditions are set to be +130°C or less. The cooling conditions are as follows: the position of the surface layer of the ingot is T β The condition is set so that the temperature is cooled from +10° C. to 300° C. or less at a cooling rate of 5° C. / s or more. Manufacturing method of titanium material.
21. The heating conditions are determined based on the results of the heat treatment simulation method according to claim 7. The method for producing a titanium material according to claim 20.
22. In the heat treatment simulation method, a prior β grain size at each time is predicted based on the temperature and phase fraction at each time obtained by the coupled analysis calculation, the heating conditions are predicted under which the average grain size of the prior β grains at a position 10 mm from the surface of the ingot is 10 mm or less and the standard deviation of the grain size of the prior β grains is 5 mm or less, and the ingot is heated according to the predicted heating conditions. The method for producing a titanium material according to claim 21.
23. The cooling conditions are determined based on the results of the heat treatment simulation method according to claim 7. The method for producing a titanium material according to any one of claims 20 to 22.
24. The time t from the end of the heating to the start of the cooling 2 is determined based on the results of the heat treatment simulation method according to claim 7. The method for producing a titanium material according to any one of claims 20 to 22.
Citation Information
Patent Citations
Hot rolling method of titanium material
JP1986159562A
Rotary applicator
JP1988072373A
Method for hot-working titanium ingot
JP1989156456A
Production of titanium material
JP1996060317A